2007
DOI: 10.1177/152692480701700411
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Barriers and Facilitators to Physical Activity in Kidney Transplant Recipients

Abstract: Motivational interventions should focus on diminishing perceived barriers in the less physically active transplant recipients and enhancing perception of health-related facilitators. Nurses should be innovative in customizing interventions, recommending structured physical activity programs, and encouraging less structured, enjoyable ways to increase activities that expend energy. Interventions with achievable outcomes and realistic expectations are more acceptable to patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 21 publications
3
48
1
Order By: Relevance
“…From our study we identified exercise as a part of the early rehabilitation program and this component is also supported by cardiovascular, biochemical, and muscle strength benefits shown by other studies (Juskowa et al, 2006;Korabiewska et al, 2007). In addition, understanding barriers and facilitators to exercise would be of benefit (Sanchez et al, 2007).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…From our study we identified exercise as a part of the early rehabilitation program and this component is also supported by cardiovascular, biochemical, and muscle strength benefits shown by other studies (Juskowa et al, 2006;Korabiewska et al, 2007). In addition, understanding barriers and facilitators to exercise would be of benefit (Sanchez et al, 2007).…”
Section: Discussionsupporting
confidence: 58%
“…Gordon et al (2005), however, argue that too much effort has been directed toward reactive, clinical efforts by transplant professionals to prevent graft rejection rather than proactive measures taken by recipients to promote kidney function. Moreover, the authors of several studies have remarked that rehabilitation should start postoperatively within a few days and that its success or lack thereof can have a marked effect on outcomes (Juskowa et al, 2006;Templin and Janek, 2006;Korabiewska et al, 2007;Sanchez et al, 2007). Randolph and Scholz (1999) also comment that to reduce costs, patients are often discharged so quickly that there is little time for education or institution of self-care or rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10] Furthermore, existing studies mostly used quantitative designs, presenting patients with questionnaires consisting of a predetermined list of possible nonadherence reasons or lifestyle problems. 5,6,[11][12][13] This approach rarely allows participants to add other difficulties they experience nor share strategies they might use to manage these risk factors. Qualitative studies using focus groups or semistructured interviews can provide a more in-depth understanding of difficulties experienced.…”
mentioning
confidence: 99%
“…Poor motivation for physical activity many also be a barrier. 96,97 Following kidney transplantation, cardiac output may be reduced due to a number of reasons such as cardiomyopathies, which could limit some types of activities such as aerobic exercise. 96 Blood pressure is also affected in kidney transplant recipients due to denervation of the transplanted kidney, so blood pressure could be higher in these individuals following exercise.…”
Section: Health Benefits In Kidney Transplant Recipientsmentioning
confidence: 99%